The Main Factors of Tourism Influencing Thai Tourists Choice to Cultural Tourism, in Khok Slung Community, Lopburi Province - เรียงหา, อัญชลี; พรหมทอง, ปิยาภา; วุฒิยา, กัญญาพัชร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purposes of this research study were (1) investigate the demographic characteristics of Thai tourists who travel to the food tourism community of Khok Salung, Lopburi Province; (2) identify the primary factors influencing Thai tourists' decisions to visit the Thai-Beng cultural community of Khok Salung, Lopburi Province; and (3) compare the demographic characteristics with the primary factors that influence Thai tourists' decisions to visit the Thai-Beng cultural community of Khok Salung, Lopburi Province. This is a quantitative study with a sample size of 400 participants, selected through random sampling. A questionnaire was used as the research instrument.The findings of the study reveal that respondents place the greatest importance on the key factors influencing their decision to visit the Thai-Beng cultural community of Khok Salung, Lopburi, particularly in terms of the attractiveness of the tourism destination, which was rated at the highest level (x̅ = 4.30, S.D. = 0.75). When considering individual factors, the most significant element influencing the decision to visit was the availability of activities that allow tourists to learn about the community’s way of life. This includes learning about indigenous knowledge, local food, handicrafts, and folk games, all of which were rated at the highest level.  Hypothesis testing revealed that age had a significance value (Sig) of 0.01*, the highest level of education had a Sig value of 0.00*, and average monthly income had a Sig value of 0.04*. These factors significantly influenced the key tourism elements affecting Thai tourists' decisions to visit the Thai-Beng cultural community of Khok Salung, Lopburi, with a statistical significance level of 0.05. For other factors, the hypotheses were rejected.